Analysis of Cross-border Mergers and Acquisitions Activities in Emerging Markets: Case Studies based on Automotive Industry of Geely and Tata Motors - Shen, Yiran (2015)
Since the last several decades, an increasing number of firms from emerging markets have joined the trend of cross-border M&As through the buying up of a high equity brand in the west, with China and India being among the most active participants. The cases from emerging market automakers are particularly looked into for providing a new insight to the previous research which seems to be irrelevant of industry groups. This research examines and explores three questions: firstly, the proactive motives and reactive motives behind the cross-border M&As of emerging market firms; secondly, the challenges during post-acquisition stage of the M&A deals; thirdly, the rationale that forms EMEs’ choice of cross-border M&As rather than equity joint venture as the entry mode of internationalisation.